VEGETATION SYNTAXONOMY AND LAND MANAGEMENT EFFECT ON METHANE AND CARBON DIOXIDE EMISSIONS FROM WETLANDS: A CASE STUDY FROM TIDAL SALT AND BRACKISH MARSH - Satyanti, Annisa; Saragih, Evi; Egan, Paul; Cid, Nuria Simon; Knecht, Elise; Euwe, Marieke (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2014)
Carbon dioxide (CO2) and methane (CH4) emission from wetlands significantly contribute to climate change and global warming. The interaction between among vegetation type, various environmental factors, and management regimes such as grazing and mowing is considered important in the calculation of CO2 and CH4 gas flux for an ecosystem. In this study, vegetation composition, CH4 and CO2 flux, soil characteristics, air temperature and humidity from the brackish marsh and salt marsh wetland ecosystems on Terschelling Island in Northern Holland were measured. We aimed to investigate the relationship between vegetation composition, grazing, and mowing on CH4 and CO2 emission. The abundance and number of plant species were higher in brackish than in salt marsh. Grazing was found to influence species richness, 39 species being found in a grazed site of brackish marsh compared to 31 species in a similar ungrazed site. CO2 fluxes in salt and brackish marsh were found to be similar while CH4 flux in the salt marsh was found to be lower than in the brackish marsh. Within the brackish marsh, a higher methane emission was recorded in the grazed zone. However the overall effect of grazing and mowing was found to be negligible for CH4 flux but is suggested to clearly reduce CO2 flux in both the salt and brackish marsh.